(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
This article describes the representation of verbal markers in interpersonal conflict, based on the reactions of the person and the link between the development of conflicts and feelings of a man were identified, the author also based Ukranian linquistics and cultural causes in political conflicts.